The state and prospects of Ukrainian literary onomastics development in the Slavic context - Колесник, Наталія; Петренко, Оксана (My University, 2021)
Literary onomastics is one of the most popular fields of Slavic onomastics. Howev- er, despite the popularity, certain terminology disagreements in literary onomas- tics still exist. The article brings up the opinion that the complexity of the object of study is not the only reason for the terminological inconsistencies. According to the tasks that the researchers set themselves in terms of literary onomastics analysis, there is a completely different purpose behind it. Given the diversity of literary texts and the functions of proper names, it considers the understanding of it as a complex multidimensional discipline to be a perspective of literary onomastics development.
STANJE RAZISKAV IN RAZVOJNE PERSPEKTIVE UKRAJINSKE LITERARNE ONOMASTIKE V SLOVANSKEM OKVIRU
Keywords: onomastics; Slavic onomastics; literary onomastics; Ukraine